Glochidion talakonense sp. nov. (Phyllanthaceae) from Seshachalam Biosphere Reserve, Andhra Pradesh, India (Bangladesh Journal of Plant Taxonomy, 2016)
Glochidion talakonense M. Sankara Rao, J. Swamy, S. Nagaraju, S.B. Padal, M. Tarakeswara Naidu, K. Chandramohan & T. Thulasiah, a new species of Phyllanthaceae from Talakona hills, Seshachalam Biosphere Reserve, Andhra Pradesh, India, is described and illustrated. It is allied to G. karnaticum Chakrab. & M. Gangop., but differs from the latter by stamens, ovary, style and fruit characters. Bangladesh J. Plant Taxon. 23(1): 59-63, 2016 (June)